Bilevel transportation problems - Duca, Dorel; Lupşa, Liana (Rev. Anal. Numér. Théor. Approx., 2001)
In this paper we formulate the bilevel transportation problem of the cost-time type and of the cost-cost type, we propose a general algorithm for solving this problems and we also give two examples.